PENINGKATAN LITERASI DASAR SISWA SEKOLAH DASAR MELALUI KEGIATAN LOMBA BACA PUISI DI DESA NGADIREJO - Krisnanda Firman Inzeani; Yahya, Levia Tivani; Ferdiansyah, Atnan; Danarrini, Pramesti; Dewi Tryanasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This community service activity aims to improve basic literacy among fifth and sixth grade students through a poetry reading competition in Ngadirejo Village. The low interest in reading literature, particularly poetry, and limited literacy activities were the reasons behind the poetry reading competition. The implementation method included planning, conducting, and evaluating the competition. The poetry reading competition was held on November 27, 2025, with six students representing fifth and sixth grades from three elementary schools in Ngadirejo Village participating. The results showed that the poetry reading competition improved literacy skills, increased student participation, and positively impacted the school's literacy culture. The poetry reading competition also encouraged teacher involvement in literacy development and led to the creation of a poetry corner. Therefore, the poetry reading competition can be an effective literacy strategy for fostering reading culture and literary appreciation among elementary school students.